Ecological Condition of Land Around Regulatory Basins of Irrigation Systems in the Dnipropetrovsk region - Maksymova, N. M.; Orlinska, O. V.; Chushkina, I. V.; Pikarenia, D. S.; Чушкіна, І. В.; Максимова, Н. М.; Орлінська, О. В.; Пікареня, Д. С. (Національний університет "Львівська політехніка", 2019)
It is shown that the NPEMFE method is possible for using to allocate water filtration zones through the ground-based dams of basins of reclamation systems. It is allow to quickly taking measures to reduce water losses and deteriorate the ecological state of the underground hydrosphere around the regulatory basins.
Keywords: regulating irrigation basin; water losses due to filtration; geophysical research